ETV5 links the FGFR3 and Hippo signalling pathways in bladder cancer - Erica di Martino (Nature Portfolio, 2019)
Abstract Activating mutations of fibroblast growth factor receptor 3 (FGFR3) are common in urothelial carcinoma of the bladder (UC). Silencing or inhibition of mutant FGFR3 in bladder cancer cell lines is associated with decreased malignant potential, confirming its important driver role in UC. However, understanding of how FGFR3 activation drives urothelial malignant transformation remains limited. We have previously shown that mutant FGFR3 alters the cell-cell and cell-matrix adhesion properties of urothelial cells, resulting in loss of contact-inhibition of proliferation. In this study, we investigate a transcription factor of the ETS-family, ETV5, as a putative effector of FGFR3 signalling in bladder cancer. We show that FGFR3 signalling induces a MAPK/ERK-mediated increase in ETV5 levels, and that this results in increased level of TAZ, a co-transcriptional regulator downstream of the Hippo signalling pathway involved in cell-contact inhibition. We also demonstrate that ETV5 is a key downstream mediator of the oncogenic effects of mutant FGFR3, as its knockdown in FGFR3-mutant bladder cancer cell lines is associated with reduced proliferation and anchorage-independent growth. Overall this study advances our understanding of the molecular alterations occurring during urothelial malignant transformation and indicates TAZ as a possible therapeutic target in FGFR3-dependent bladder tumours.